Development and creation of the electromagnetic separator for isotope separation in the system of opposing axisymmetric magnetic fields with two field reverses - Yegorov, A.M.; Lymar’, A.G.; Nikolaichuk, L.I.; Popov, V.A.; Bondarenko, L.A.; Tutubalin, A.I.; Nemashkalo, O.V.; Krivchenko, O.V. (Вопросы атомной науки и техники, 2013)
The paper reports the results of work on creation of a setup for isotope separation in the system of opposing axisymmetric magnetic fields with two field reverses. Consideration is given to a real possibility of improving the e±ciency of the electromagnetic separator and its resolving power in the double-reverse magnetic field system. It is demonstrated that the use of the opposing axisymmetric field system may substantially reduce the energy consumption during the process of isotope separation. The estimated magnetic field of the facility attests to a possibility of molybdenum isotope separation and isolation of high-purity ⁹⁸Mo and ¹⁰⁰Mo isotopes required for production of the ⁹⁹Mo/⁹⁹Tc generator, most widely used in modern medicine. Наводяться результати робiт по створенню установки для роздiлення iзотопiв у системi зустрiчних аксiально-симетричних магнiтних полiв з двома реверсами поля. Обговорюється реальна можливiсть пiдвищення продуктивностi електромагнiтного сепаратора i його роздiльної здатностi в системi магнiтного поля з подвiйним реверсом. Показано, що використання системи зустрiчних аксiально-симетричних полiв дасть можливiсть iстотно знизити енерговитрати в процесi роздiлення iзотопiв. Наведена оцiнка магнiтного поля на установцi свiдчить про можливiсть роздiлення iзотопiв молiбдену i видiлення iзотопiв ⁹⁸Mo i ¹⁰⁰Mo високої чистоти, необхiдних для отримання найбiльш вживаного в сучаснiй медицинi генератора ⁹⁹Mo/⁹⁹Tc. Приводятся результаты работ по созданию установки для разделения изотопов в системе встречных аксиально-симметричных магнитных полей с двумя реверсами поля. Обсуждается реальная возможность повышения производительности электромагнитного сепаратора и его разрешающей способности в системе магнитного поля с двойным реверсом. Показано,что использование системы встречных аксиально-симметричных полей даст возможность существенно снизить энергозатраты в процессе разделение изотопов. Приведенная оценка магнитного поля на установке свидетельствует о возможности разделения изотопов молибдена и выделения изотопов ⁹⁸Mo и ¹⁰⁰Mo высокой чистоты, необходимых для получения наиболее применяемого в современной медицине генератора ⁹⁹Mo/⁹⁹Tc.